PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, PERSEPSI MANFAAT, PERSEPSI RISIKO, DAN PERSONALISASI TERHADAP MINAT GENERASI Z MENGGUNAKAN PEER TO PEER LENDING - Suliantini, Ketut Ayu; Dewi, Gst. Ayu Ketut Rencana Sari (Vokasi : Jurnal Riset Akuntansi, 2021)
This study aims to determine the effect of perceived convenience use, perceived benefit, perceived risk, and personalization of interest Generation Z uses peer to peer lending. This research uses Technology Acceptance (TAM) is a theory commonly used to analyze and explain individual acceptance of a technology. This study took a sample of students of the 2018 S1 Accounting study program Faculty of Economics at Ganesha University of Education who has used peer to peer lending by distributing online questionnaires using google forms. The data was obtained through the probability sampling method with the number of a sample of 166 respondents. The test is carried out using SPSS version 26.0 program. The results of hypothesis testing and discussions that have been carried out can conclusions are drawn, namely (1) the perception of ease of use has a positive effect on student interest in using peer-to-peer lending, (2) perception benefits have a positive effect on student interest in using peer-topeer lending, (3) risk perception has a negative effect on student interest using peer-to-peer lending, and (4) personalization has a positive effect on student interest in using peer-to-peer lending.